Synthesis and Characterization of Some Novel Schiff Base Complexes of Oxovanadium(IV) Cation - A. K. Yadava; H. S. Yadav; Sanjay Singh; U. S. Yadav; D. P. Rao (Journal of Chemistry)
A series of oxovanadium(IV) complexes of the type [VO(mac)]SO4 (where mac = tetraazamacrocyclic ligands derived from condensation of 4,4,4-trifluro-1-(2-furyl)-1,3-butanedione or 4,4,4-trifluro-1-(2-thenyl)-1,3-butanedione with p-phenylenediamine and their reaction with β-diketones) have been prepared using oxometal ion of vanadium as kinetic template. These complexes have been ascertained by electrical conductance, magnetic moment, elemental analyses, infrared, e.s.r. and electronic spectral data. All the oxovanadium(IV) complexes are five-coordinate ones.